Metabolomics screening of oxygen-glucose deprived neurons as a model of hypoxic-ischemic encephalopathy for newborns - Gaspar, Diana (2022)
Hypoxic-ischemic encephalopathy (HIE) is considered one of the most frequent causes of brain injury in newborns. This injury results from an event of asphyxia that can occur before, during, or after birth. HIE is a devastating episode that affects 1 to 8 infants per 1000 live births in developed countries, and this incidence is higher in underdeveloped countries. Cerebral palsy is one of the conditions most frequently associated with HIE. Currently, the diagnosis of HIE is based on clinical criteria that make it inaccurate, slow and inaccessible in several hospital units and countries. Regarding treatment, therapeutic hypothermia is considered the standard of care for newborns with HIE, but it has a small therapeutic window, within 6 hours after birth. Thus, it is essential and urgent to proceed to the discovery of biomarkers to help in the diagnosis of HIE. In this way, the aim of this study was to perform a metabolomics profiling of primary cultures of cerebrocortical neurons submitted to two models of neuronal death, a cellular model of HIE (oxygen and glucose deprivation (OGD)) and a glutamate-based model, to identify potential biomarkers that may be used in the clinical diagnosis of HIE. For this purpose, initially, primary cultures of neurons isolated from the cerebral cortex of Wistar rat embryos (E17-18) were prepared and at day in vitro 9, the cells were submitted to an OGD insult (2 hours) and a glutamate stimulus (20 minutes). After 24 hours (for the OGD insult) and after 6 hours (for the glutamate stimulus), the cellular proteome and metabolome were extracted, followed by precipitation of the proteins with methanol. Once the samples were prepared, a metabolomics analysis was performed by liquid chromatography coupled to tandem/hybrid mass spectrometry, in order to identify potential metabolites of interest. In this study, two analyses were performed: an untargeted metabolomics analysis and a targeted metabolomics analysis. After data processing and analysis, the metabolites tryptophan, β-NAD, FAD, and sphinganine were identified as potential biomarkers and sphingolipid metabolism as a possible altered metabolic pathway. These results may contribute to translational biomarker profiling for HIE. In the future, since the results were obtained from in vitro models, it is necessary to further validate them in the animal model of HIE and then in humans. The metabolomics analysis of the secretomes will allow to infer on circulating biomarkers.